Proceedings of the 11th International Workshop on Polarized Sources and Targets : Tokyo, Japan, 14-17 November 2005 - Uesaka, Tomohiro (World Scientific, 2007)
Polarized beams and targets have been irreplaceable tools in nuclear and particle physics experiments for a long time and have provided us rich information on the role played by spin-degrees of freedom in the sub-nuclear world. In addition, techniques to obtain large nuclear polarization have recently been applied to new fields such as materials and medical sciences. The scope of these proceedings covers recent progress of state-of-the-art techniques in spin polarization, the cryogenic method, the atomic beam method, the optical pumping method and the nuclear reaction method.